The European nutrition research landscape: diversity and perspectives. - Perez-Cueto, Federico J.A.; Brennan, Sarah F.; Laitinen, Kirsi; Diercks, Jutta; Spiroski, Igor; Katić, Mašenjka; Fallaize, Rosalind; Garin, Jean-Paul; Cvejic, Jelena Helene; Pourshahidi, L. Kirsti; Bordoni, Alessandra; Ockhuizen, Theo; et al. (European Journal of Nutrition, 2025)
Purpose: The diversification of Nutrition Sciences (NS) in recent decades has highlighted the need to review current practices in relation to funding, communication and interaction with stakeholders. The Federation of European Nutrition Societies (FENS) Presidential Activity “Improving standards in the science of nutrition” established three working groups to develop consensus documents. This paper is part of Working Group 2 (WG2) “Organisation, Capabilities and Funding” and aims at describing the European Nutrition Research Landscape, addressing its diversity, challenges and future perspectives. Methods: WG2 developed two rounds of questionnaires designed to map the current funding architecture in FENS member countries. Questionnaires were administered to representatives of national NS member societies in 2022 and desk research was carried out to describe the main European Union (EU) sources of funding. Qualitative data analysis was performed on questionnaire data collected and agreed and approved by WG2. Results: 42% of representatives responded to the first round of data collection, and 30% to the second round of data collection. Results indicate that the NS field is mainly funded by public agencies, private actors, and by contract. Most calls are multi-disciplinary and the majority of societies were aware of risks posed by engagement with the private sector and financial conflicts of interest (COI). Conclusion: This exercise provides an insight into the funding landscape across Europe for NS and highlights the uniquely multifaceted funding sources and dynamics across the continent. This work also underscores the challenges NS faces and progress made with issues surrounding COI and the associated reputation of NS.